Strategic foresight framework for addressing agency in sustainability transitions: a co-creation approach - Matti, Cristian; Bontoux, Laurent; Jensen, Kathrine (Frontiers in Sustainability, 2025)
This paper presents a novel methodological approach that integrates strategic foresight with sustainability transitions frameworks to explore how different forms of agency shape transition pathways. The research methodology employed include the development of foresight scenarios addressing sustainability, the X-curve framework for mapping possible transition pathways for a sustainable EU 2050, and agency analysis to identify strategic areas of interventions and understanding systemic policy mixes over time. This work was performed in the context of the preparation of the European Commission’s Annual Strategic Foresight Report 2023. Additionally, through empirical application across three distinct contexts, this paper demonstrates how strategic foresight can generate actionable knowledge for sustainability transitions while maintaining methodological rigor. The study advances the theoretical understanding of agency in sustainability transitions by showing how different actors can be strategically engaged through interventions aimed at shaping, navigating, and orchestrating transition pathways over time. Our findings reveal that successful transitions require balancing the agency of established institutional actors with emerging stakeholders who may lack formal authority but bring crucial perspectives and capabilities. The study emphasizes the importance of agency of multiple actors in sustainability transitions, highlighting their capacity to act and collaborate in shaping a sustainable future. The conclusions and recommendations stress the need for strong government leadership, multilevel coordination, the roll out of systemic policy mixes and a new social contract underpinned by democratic governance. The flexibility of the methodological approach allows adaptation to different institutional contexts through co-creation while maintaining coherence in how agency dealt with. This research contributes to both theoretical development and practical policy implementation by providing a structured yet adaptable strategic foresight approach to investigate how different forms of agency can effectively be combined to drive sustainability transitions.